Entrepreneurial Orientation Increases Womenpreneur Business Performance: The Role of Customer-Centric Discovery, Market Responsiveness and Digital Literacy - Zulkifli, Zulkifli; Rahmawati, Rahmawati; Indriastuti, Herning; Achmad, Gusti Noorlitaria (International Review of Management and Marketing, 2026)
The research is motivated by the importance of women entrepreneurs’ role in driving economic growth in the era of global competition, which demands adaptation to market and technological changes. Consequently, they are required to identify customer needs and respond quickly to market demands enabled by digitalization. The contribution of research on customer-centric discovery and market responsiveness to ensure women entrepreneurs achieve superior business performance and fill the research gap between entrepreneurial orientation and business performance. A quantitative approach with a purposive sampling technique of 384 female MSME actors registered with the Cooperative and MSME Office in several cities in East Kalimantan, Indonesia. Data analysis using (PLS-SEM). The results of the study indicate that entrepreneurial orientation and customer-centric discovery have a significant effect. Customer-centric discovery has a significant effect on market responsiveness. Customer-centric discovery has a significant effect on the womenpreneur’s performance. Market responsiveness has no significant impact on womenpreneur performance. Market responsiveness does not mediate the relationship between entrepreneurial orientation and womenpreneur performance, nor does it mediate the relationship between customer discovery and performance. Digitalization significantly moderates the relationship between customer-centric discovery and performance. This research provides a theoretical contribution by strengthening the role of digital literacy as a reinforcing factor in the customer-centric discovery relationship model on performance, as well as a practical contribution in the form of policy recommendations for women-owned MSMEs.